Multiple Wnts are involved in Hydra organizer formation and regeneration - Lengfeld, Tobias; Watanabe, Hiroshi; Simakov, Oleg; Özbek, Suat; Holstein, Thomas W. (Developmental biology, 2009)
Wnt genes and β-Catenin signaling are involved in axial patterning processes in vertebrate embryogenesis in setting up the Spemann-Mangold organizer in amphibian embryos. An organizer with a similar function is present in the hypostome of an adult Hydra polyp. Previously, a Hydra ortholog of Wnt3 (HyWnt3), which is expressed in the hypostome, has been described. Here, ten additional Hydra Wnt genes have been identified. Of these, six (HyWnt1, -7, -9/10a, -9/10c, -11, and -16) are expressed in the adult hypostome. And, as is HyWnt3, these six Wnt genes are also expressed when a new head organizer is formed during head regeneration and bud formation. The kinetics of Wnt gene expressions during head regeneration suggests that a cascade of consecutive Wnt activation accompanies regeneration, and HyWnt3 begins this cascade. Recombinant HyWnt3 protein induced body column tissue to undergo head formation. It also increased the head formation capacity in the head regeneration-deficient mutant strain reg-16 to that of wild-type strains. In addition our data reveal striking similarities in the molecular basis of the organizer in Hydra and axis polarization in chordates (e.g. Spemann's organizer) as well as it's role in regeneration suggesting a conserved function of Wnt signaling in setting up this ancient metazoan signaling center.
Gesehen am 26.06.2017